Analisis terhadap Metode Berteologi Kalangan Pentakosta dari Trialektika Amos Yong menurut Triperspektif John Frame - Antonius (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2022)
Pentecostalism is one of the fast-growing traditions that is distinctive in its theological method. Some Pentecostals also claim that they are an evangelical church. This claim can lead to debates and blur the meaning of evangelical as if there is no difference between the two. This difference cannot be seen only from the church’s status but from the method of theology that underlies it. Therefore, this study will compare the theological method of the Pentecostals-Charismatics, represented by Amos Yong, and the theological method of the Reformed, represented by John M. Frame. The purpose of this comparison is to try to find common ground and balance between the two approaches. Frame’s Triperspectivalism method can give room for Yong’s Trialectic method to see the Holy Spirit-Word-Community aspect from the normative, situational, and existential lenses of theology as three inseparable parts. Thus, it is hoped that there can be harmony in theological methods between the Pentecostal-Charismatic tradition and the Reformed tradition.